Stative vs. Eventive Participles in an Arbëresh Variety under the Influence of the Italian Language - Giuseppina Turano (Languages, 2023)
In this paper, I explore the properties and the uses of the past participles in the Arbëresh variety of S. Nicola dell’Alto, an Albanian dialect still spoken in Southern Italy, which has been in contact with Italo-Romance varieties for more than five centuries. The data are discussed in comparison to standard Albanian and the contact language, Italian. In Albanian grammar, there is only one type of participle: the past participle. It has both verbal and adjectival properties. As a verbal form, the participle is used in compound and in periphrastic tenses, in combination with both the auxiliaries KAM ‘have’ and JAM ‘be’. It can also be used in combination with other particles to create non-finite verbal forms such as gerund or infinitive or to build up temporal expressions. Finally, it can also be used after some modal impersonal verbs. Verbal participles never show agreement. Albanian participles can also be adjectival. All the adjectives derived by a participial verb take a linking article and always agree with the noun they modify in gender, number, Case and definiteness. The formal distinction of the verbal participles from adjectival participles seems to correlate with the aspectual properties of the construction: a verbal participle appears in eventive structures, whereas an adjectival participle occurs in stative structures. But, as we shall see, this is not always the case. Arbëresh participles have maintained the same morphological and syntactical properties of Albanian. They can be used both in stative and in eventive contexts, but in Arbëresh eventive passives, which are built up as in Italian rather than as in Albanian, the adjectival participles are always inflected. Agreement is obligatory in all the contexts where it is in Italian. This is a clear contact-induced change. The data presented in this paper show that Arbëresh, on the one hand, preserves features of Albanian grammar, whereas, on the other hand, it has undergone changes under the influence of the surrounding Italo-Romance varieties.